Estimating the outcome of an Active Phase in the Military Conflict on Eastern Ukraine based on the Sugeno Fuzzy Integral - Bocharnikov, Victor; Sveshnikov, Sergey; Timoshenko, Radion (Yugoslav Journal of Operations Research; Vol 32 No 1 (2022), 2022)
A military conflict (especially its active phase) is a time of maximum exertion of all the powers of the state and society, a time that requires quick and correct decisions from state bodies. The quality of these decisions is largely determined by the estimation adequacy of the current situation. As the analysis shows, modern military conflicts start suddenly and develop rapidly. The official informing system turns out to be ineffective, what leads to numerous mistakes in decision-making. In addition, modern military conflicts are of a hybrid nature. The outcome of such military conflicts depends on many factors of a non-military nature, for example, the quality of governance, support from the population, international assistance. These factors are often formulated qualitatively (linguistically), and the conditions of the active phase of a military conflict do not give time to check the adequacy of quantitative data. Therefore, the estimation of the current situation in a military conflict requires solving two problems. Firstly, the complexity of quantitative description the situation characteristics and lack of reliable data requires taking into account uncertainty and the use of all available sources of information. Secondly, a large number of these characteristics makes it difficult to analyze and requires the calculation of some generalized characteristic. Therefore the authors proposed using the methods of fuzzy integral calculus to describe partial characteristics and calculate a generalized characteristic, which is an estimation of the success of the outcome of an active phase of a military conflict from the view-point of the attacking participant. The authors have solved the following subproblems: identification of structure and parameters of standard for estimating; choice of the observation channel of the characteristics of the current situation; constructing the algorithm for estimations generalization. The authors used proposed algorithm to estimate the results of hostilities in eastern Ukraine in July 2014.